Measuring the Interdisciplinarity and Collaboration Perceptions of U.S. Scientists, Engineers, and Educators - Katherine R. McCance; Margaret Blanchard (SAGE Publishing, 2024)
Interdisciplinarity has the potential to lead to more innovation and advances in knowledge than are possible from a single discipline. Yet, little is known about interdisciplinary collaborations and the perceptions of those involved. This quantitative study investigated the perceptions of U.S. faculty, staff, postdocs, and graduate students involved in education and science/engineering collaborations. Exploratory factor analysis was conducted for two modified scales, Collaboration Perceptions (CP; n = 117; 17 items; α = .923) and Interdisciplinarity Perceptions (IP; n = 119; 11 items; α = .852). Participants' perceptions of collaboration and interdisciplinarity were strongly positive and did not significantly differ based on demographic factors (e.g., gender, discipline, role). Perceptions were influenced by collectivist orientation; the high collectivism group had significantly more positive perceptions of collaboration and interdisciplinarity, and collectivist orientation was positively and significantly correlated with CP and IP scores. Implications and recommendations for interdisciplinary collaborations will be discussed.